The analysis of ocular movement for the dynamic postural control of turn motion on the balance beam - Kim, Y. J.; So, J.-M.; Lim, J.-T. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study demonstrated the importance of dynamic postural balancing and ocular movement in a turn motion on the balance beam using a manufactured wireless EOG measuring system with three female gymnasts. This study found that among the dynamic postural control variables, angular displacement and ocular movement were closely related. During a turn motion, the ocular movement was in opposite direction of the angular displacement of head and trunk along the medio-lateral axis. This resulted from the gymnast`s effort to stare at the end of the balance beam or the front in order to keep balance. The change of angular displacement of head around the medio-lateral axis and vertical axis was in opposite direction of the ocular movement. When the motion was successful, the gymnasts performed a spotting motion.